High-strength wear-resistant liquid crystal polymer fiber and preparation method thereof
By covering the outer crosslinked polymer on the inner polymer surface of the liquid crystal polymer fiber and forming a crosslinking network through microwave heating treatment, the fiber's processing and mechanical properties are solved, and the bending, shear and strength resistance is achieved.
Patent Information
- Application Number
- CN202411789754.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
AI Technical Summary
Liquid crystal polymer fibers are prone to longitudinal stratification during processing and are easily damaged when bending and shearing, affecting their application performance.
Using a combination of inner layer polymer and outer layer crosslinking polymer coated on its surface, the mechanical properties of the fiber are enhanced by crosslinking polymers perpendicular to the fiber axis, and a uniform and dense crosslinking network wear-resistant layer is formed by microwave heating treatment.
It effectively improves the bending and shear resistance of liquid crystal polymer fibers, avoids longitudinal layering, and improves the strength and modulus of the fibers in the fiber axis direction.
Smart Images

Figure SMS_3 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a high-strength and wear-resistant liquid crystal polymer fiber and a preparation method thereof. Background Art
[0002] Liquid crystal polymer fiber is a fiber with comprehensive properties such as high strength and modulus, high temperature resistance, self-flaming retardant, chemical resistance, radiation resistance, and strong dimensional stability. It can be used in aerospace, armor protection, ship cables, etc. Compared with the three traditional high-performance fibers (aramid, ultra-high molecular weight polyethylene, and carbon fiber), liquid crystal polymer fiber can be produced by melt spinning, which can reduce costs and pollution. In addition, liquid crystal polymer fiber does not require post-stretching and other processes during preparation, which can simplify the processing technology.
[0003] However, the molecular chain of liquid crystal polymer has a rigid chain structure. During the process of preparing fibers, the molecular chain will be oriented along the fiber axis to form a highly ordered microfiber structure, and there will be strong covalent bonds along the fiber direction to give the fiber a higher breaking strength and modulus. In the direction perpendicular to the fiber axis, since there are no covalent bonds or hydrogen bonds between the molecular chains, liquid crystal polymer fibers are prone to longitudinal stratification during processing. At the same time, the fibers are easily damaged when subjected to bending and shearing, which seriously affects the application performance of the fibers. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to provide a high-strength and wear-resistant liquid crystal polymer fiber and a preparation method thereof, which can effectively improve the bending and shear resistance of the fiber and avoid longitudinal stratification during processing.
[0005] In order to achieve the above purpose, one of the technical solutions adopted by the present invention is: a high-strength wear-resistant liquid crystal polymer fiber, comprising an inner layer polymer and an outer layer cross-linked polymer coated on the surface of the inner layer polymer; the molecular structure of the outer layer cross-linked polymer is: .
[0006] Specifically, the inner layer polymer accounts for 80-90% of the cross-sectional area of the high-strength and wear-resistant liquid crystal polymer fiber, and the outer layer cross-linked polymer accounts for 10-20% of the cross-sectional area of the high-strength and wear-resistant liquid crystal polymer fiber.
[0007] An outer layer of cross-linked polymer is coated on the surface of the inner layer of polymer, and the cross-linking effect between polymer molecules in the direction perpendicular to the fiber axis is utilized, which can not only enhance the mechanical properties of the fiber in the direction perpendicular to the fiber axis, thereby improving the bending and shear resistance of the high-strength and wear-resistant liquid crystal polymer fiber, and avoiding the phenomenon of longitudinal stratification of the high-strength and wear-resistant liquid crystal polymer fiber in the subsequent processing; it can also restrict the relative slippage between polymer molecules when the high-strength and wear-resistant liquid crystal polymer fiber is stretched by an external force in the direction of the fiber axis, thereby enhancing the strength and modulus of the fiber in the direction of the fiber axis.
[0008] Specifically, the components of the outer layer cross-linked polymer include an outer layer polymer, a cross-linking agent, and a catalyst.
[0009] Specifically, the components of the outer layer polymer include monomers with naphthalene rings, diacid monomers, and monomers with double bonds.
[0010] More specifically, based on molar weight, the composition of the outer layer polymer includes 60-70% of a monomer having a naphthalene ring, 10-20% of a diacid monomer, and 10-20% of a monomer having a double bond.
[0011] A double bond-bearing monomer is introduced into the outer layer polymer so that the outer layer polymer can undergo a cross-linking reaction with a cross-linking agent.
[0012] Specifically, the naphthalene ring-containing monomer is at least one of 2-hydroxy-6-naphthoic acid, 6-hydroxy-1-naphthoic acid, 7-hydroxy-2-naphthoic acid, and 5-hydroxy-2-naphthoic acid.
[0013] Specifically, the diacid monomer is at least one of 5-methylisophthalic acid, 4,4-biphenyldicarboxylic acid, and terephthalic acid.
[0014] Furthermore, the double bond-bearing monomer is at least one of 2-allylbenzene-1,4-diol and 4-allylcatechol.
[0015] Further, the cross-linking agent is vinyl-POSS.
[0016] Furthermore, the amount of cross-linking agent added is 5-10% of the mass of the outer layer polymer.
[0017] Furthermore, the catalyst is at least one of zinc chloride, aluminum chloride and tin chloride.
[0018] Specifically, the amount of the catalyst added is 0.002-0.004% of the mass of the cross-linking agent.
[0019] The introduction of crosslinking agents in the outer crosslinked polymer layer can significantly improve the wear resistance and UV aging resistance of high-strength and wear-resistant liquid crystal polymer fibers, which is beneficial for the use of high-strength and wear-resistant liquid crystal polymer fiber products in extreme environments such as oceans and long-term exposure. At the same time, the introduction of crosslinking agents can also make high-strength and wear-resistant liquid crystal polymer fibers have a lower dielectric constant, which can meet the needs of applications such as high-frequency cables and copper-clad laminates.
[0020] To further explain, the molecular structure of the inner polymer is: .
[0021] Specifically, the components of the inner layer polymer include naphthalene ring-bearing monomers, benzene ring-bearing monomers, and diphenol monomers.
[0022] Specifically, based on molar weight, the components of the inner layer polymer include 60-70% of naphthalene ring-containing monomers, 10-20% of benzene ring-containing monomers, and 10-20% of diphenol monomers.
[0023] Specifically, the naphthalene ring-containing monomer is at least one of 2-hydroxy-6-naphthoic acid, 6-hydroxy-1-naphthoic acid, 7-hydroxy-2-naphthoic acid, and 5-hydroxy-2-naphthoic acid.
[0024] Specifically, the benzene ring-containing monomer is at least one of p-hydroxybenzoic acid, m-hydroxybenzoic acid, and 4-hydroxyphenylacetic acid.
[0025] Specifically, the diphenol monomer is at least one of hydroquinone, resorcinol and 1,4-benzene.
[0026] Furthermore, the inner layer polymer and the outer layer polymer are both prepared by melt copolymerization.
[0027] Furthermore, the preparation of the inner layer polymer and / or the outer layer polymer includes: adding the components of the inner layer polymer / outer layer polymer into a reaction container, heating to 200~250°C under nitrogen flow, and stirring at a speed of 400~600r / min for 30~60min; adding an esterification catalyst, continuing to stir for 30~60min, evacuating, and melt copolymerizing for 1~2h; after the reaction is completed, naturally cooling to room temperature to obtain the inner layer polymer / outer layer polymer.
[0028] It should be noted that after naturally cooling to room temperature, the inner layer polymer / outer layer polymer is a block solid. In order to better perform subsequent extrusion operations, the inner layer polymer / outer layer polymer can be crushed to obtain a powdered inner layer polymer / outer layer polymer.
[0029] Furthermore, the esterification catalyst is at least one of calcium acetate, magnesium acetate, and zinc acetate.
[0030] Specifically, the amount of the esterification catalyst added is 0.005-0.01% of the amount of the naphthalene ring-containing monomer added.
[0031] The second technical solution adopted by the present invention is: a method for preparing high-strength and wear-resistant liquid crystal polymer fibers, comprising the following steps: (1) preparing an inner layer polymer and an outer layer polymer respectively; (2) uniformly mixing the outer layer polymer, the crosslinking agent, and the catalyst to prepare a crosslinking mixture; extruding the inner layer polymer and the crosslinking mixture separately and supplying them to a sheath-core composite spinning assembly; (3) The inner layer polymer and the cross-linked mixture are sequentially ejected through the spinneret of the core-skin composite spinning assembly to form primary fibers; (4) The primary fibers are simultaneously post-treated to obtain high-strength and wear-resistant liquid crystal polymer fibers.
[0032] Furthermore, in step (3), the inner layer polymer and the cross-linked mixture are sequentially sprayed so that the cross-linked mixture can be coated on the surface of the inner layer polymer.
[0033] Furthermore, in step (3), the hole diameter of the spinneret is 0.1-0.3 mm.
[0034] Furthermore, in step (4), the post-treatment includes microwave radiation treatment and heating treatment; the microwave radiation power is 200~500W; the heating temperature is 150~180℃, and the post-treatment time is 2~4h.
[0035] Furthermore, the microwave heating treatment in step (4) can cause the outer layer cross-linked polymer to undergo a cross-linking reaction on the surface of the inner layer polymer, thereby improving the bending and shear resistance of the high-strength wear-resistant liquid crystal polymer fiber; wherein the microwave radiation treatment can reduce the activation performance of the reactants, increase the diffusion rate of the reactants, and be beneficial to the degree of cross-linking, thereby forming a uniform and dense cross-linked network wear-resistant layer (i.e., the outer layer cross-linked polymer) on the surface of the inner layer polymer; at the same time, the heating treatment is beneficial to improving the degree of polymerization of the inner layer polymer, increasing the molecular weight of the polymer, and thereby optimizing the mechanical properties of the high-strength wear-resistant liquid crystal polymer fiber. In addition, the microwave heating treatment can also greatly reduce the reaction time and improve the production efficiency of the high-strength wear-resistant liquid crystal polymer fiber. DETAILED DESCRIPTION
[0036] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more explicit definition of the protection scope of the present invention. It should be noted that the following embodiments are for a better understanding of the present invention, are not limited to the best embodiments, and do not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0037] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0038] In addition, if the specific experimental steps or conditions are not specified in the examples, the operations or conditions of the conventional experimental steps described in the literature in the art can be carried out. The numerical ranges shown by "~" in the examples indicate the ranges containing the values recorded before and after "~" as the minimum and maximum values, respectively. If the manufacturers of the reagents or instruments are not specified, they are all conventional reagent products that can be obtained commercially.
[0039] The present invention provides a high-strength and wear-resistant liquid crystal polymer fiber, and a preparation method thereof comprises the following steps: (1) preparing an inner layer polymer and an outer layer polymer respectively; (2) uniformly mixing the outer layer polymer, the crosslinking agent, and the catalyst to prepare a crosslinking mixture; extruding the inner layer polymer and the crosslinking mixture separately and supplying them to a sheath-core composite spinning assembly; (3) The inner layer polymer and the cross-linked mixture are sequentially ejected through the spinneret of the core-skin composite spinning assembly to form primary fibers; (4) Post-processing the as-spun fibers to obtain high-strength and wear-resistant liquid crystal polymer fibers.
[0040] In some embodiments, in step (1), the components of the outer layer polymer include monomers with naphthalene rings, diacid monomers, and monomers with double bonds.
[0041] In some embodiments, in step (1), the components of the outer layer polymer include, by molar weight, 60-70% of a naphthalene ring-containing monomer, 10-20% of a diacid monomer, and 10-20% of a double bond-containing monomer.
[0042] A double bond-bearing monomer is introduced into the outer layer polymer so that the outer layer polymer can undergo a cross-linking reaction with a cross-linking agent.
[0043] In some embodiments, the naphthalene ring-bearing monomer is at least one of 2-hydroxy-6-naphthoic acid, 6-hydroxy-1-naphthoic acid, 7-hydroxy-2-naphthoic acid, and 5-hydroxy-2-naphthoic acid.
[0044] In some embodiments, the diacid monomer is at least one of 5-methylisophthalic acid, 4,4-biphenyldicarboxylic acid, and terephthalic acid.
[0045] In some embodiments, the monomer having a double bond is at least one of 2-allylbenzene-1,4-diol and 4-allylcatechol.
[0046] In some embodiments, in step (1), components of the inner layer polymer include naphthalene ring-containing monomers, benzene ring-containing monomers, and diphenol monomers.
[0047] In some embodiments, in step (1), the components of the inner layer polymer include, by molar weight, 60-70% of naphthalene ring-containing monomers, 10-20% of benzene ring-containing monomers, and 10-20% of diphenol monomers.
[0048] In some embodiments, the naphthalene ring-bearing monomer is at least one of 2-hydroxy-6-naphthoic acid, 6-hydroxy-1-naphthoic acid, 7-hydroxy-2-naphthoic acid, and 5-hydroxy-2-naphthoic acid.
[0049] In some embodiments, the benzene ring-bearing monomer is at least one of p-hydroxybenzoic acid, m-hydroxybenzoic acid, and 4-hydroxyphenylacetic acid.
[0050] In some embodiments, the diphenol monomer is at least one of hydroquinone, resorcinol, and 1,4-benzene.
[0051] In some embodiments, the inner layer polymer and the outer layer polymer are both prepared by melt copolymerization.
[0052] In some embodiments, the preparation of the inner layer polymer and / or the outer layer polymer includes: adding the components of the inner layer polymer and / or the outer layer polymer into a reaction container, heating to 200~250°C under nitrogen conditions, and stirring at a speed of 400~600r / min for 30~60min; adding an esterification catalyst, continuing to stir for 30~60min, evacuating, and melt copolymerizing for 1~2h; after the reaction is completed, naturally cooling to room temperature to obtain the inner layer polymer and / or the outer layer polymer.
[0053] It should be noted that after naturally cooling to room temperature, the inner layer polymer / outer layer polymer is a block solid. In order to better perform subsequent extrusion operations, the inner layer polymer / outer layer polymer can be crushed to obtain a powdered inner layer polymer / outer layer polymer.
[0054] In some embodiments, the esterification catalyst is at least one of calcium acetate, magnesium acetate, and zinc acetate.
[0055] In some embodiments, the amount of the esterification catalyst added is 0.005-0.01% of the amount of the naphthalene ring-bearing monomer added.
[0056] In some embodiments, in step (2), the cross-linking agent is vinyl-POSS.
[0057] In some embodiments, in step (2), the amount of cross-linking agent added is 5-10% of the mass of the outer layer polymer.
[0058] In some embodiments, in step (2), the catalyst is at least one of zinc chloride, aluminum chloride, and tin chloride.
[0059] In some embodiments, in step (2), the amount of catalyst added is 0.002-0.004% by weight of the cross-linking agent.
[0060] The introduction of crosslinking agents in the outer crosslinked polymer layer can significantly improve the wear resistance and UV aging resistance of high-strength and wear-resistant liquid crystal polymer fibers, which is beneficial for the use of high-strength and wear-resistant liquid crystal polymer fiber products in extreme environments such as oceans and long-term exposure. At the same time, the introduction of crosslinking agents can also make high-strength and wear-resistant liquid crystal polymer fibers have a lower dielectric constant, which can meet the needs of applications such as high-frequency cables and copper-clad laminates.
[0061] In some embodiments, in step (3), the hole diameter of the spinneret is 0.1-0.3 mm.
[0062] In some embodiments, in step (3), the inner layer polymer and the cross-linked polymer are sequentially sprayed so that the cross-linked polymer is coated on the surface of the inner layer polymer.
[0063] In some embodiments, in step (4), the post-treatment includes microwave radiation treatment and heating treatment; the microwave radiation power is 200-500 W; the heating treatment temperature is 150-180° C., and the post-treatment time is 2-4 h.
[0064] The microwave heating treatment in step (4) can make the outer layer cross-linked polymer undergo a cross-linking reaction on the surface of the inner layer polymer, thereby improving the bending and shear resistance of the high-strength wear-resistant liquid crystal polymer fiber; wherein, microwave radiation treatment can reduce the activation performance of the reactants, increase the diffusion rate of the reactants, and be beneficial to the degree of cross-linking, thereby forming a uniform and dense cross-linked network wear-resistant layer (i.e., the outer layer cross-linked polymer) on the surface of the inner layer polymer; at the same time, through heating treatment, it is beneficial to improve the polymerization degree of the inner layer polymer, increase the molecular weight of the polymer, and thereby optimize the mechanical properties of the high-strength wear-resistant liquid crystal polymer fiber. In addition, microwave heating treatment can also greatly reduce the reaction time and improve the production efficiency of the high-strength wear-resistant liquid crystal polymer fiber.
[0065] Example 1 Liquid crystal polymer fibers were prepared as follows: (1) preparing an inner layer polymer and an outer layer polymer respectively, wherein the inner layer polymer is prepared as follows: adding 60 mol% of 2-hydroxy-6-naphthoic acid, 20 mol% of p-hydroxybenzoic acid, and 20 mol% of hydroquinone into a reaction kettle, passing nitrogen to deoxygenate, heating to 200°C, and stirring at a speed of 500 r / min for 50 min; after uniform mixing, adding calcium acetate, continuing to stir for 50 min, evacuating, and melt copolymerizing for 2 h, wherein the amount of calcium acetate added is 0.005% of the mass of 2-hydroxy-6-naphthoic acid; after the reaction is completed, naturally cooling to room temperature to obtain the inner layer polymer, and then crushing the inner layer polymer to obtain inner layer polymer powder.
[0066] The outer layer polymer is prepared as follows: 60 mol% of 2-hydroxy-6-naphthoic acid, 20 mol% of 5-methylisophthalic acid, and 20 mol% of 2-allylbenzene-1,4-diol are added to a reactor, nitrogen is passed to deoxygenate, and the temperature is raised to 200°C, and stirred at a speed of 500 r / min for 50 minutes; after uniform mixing, calcium acetate is added, stirring is continued for 50 minutes, vacuum is drawn, and melt copolymerization is reacted for 2 hours, and the amount of calcium acetate added is 0.005% of the mass of 2-hydroxy-6-naphthoic acid; after the reaction is completed, it is naturally cooled to room temperature to obtain the outer layer polymer. Then, the outer layer polymer is crushed to obtain the outer layer polymer powder.
[0067] (2) Adding vinyl POSS and zinc chloride to the outer layer polymer powder to form a cross-linked mixture, wherein the amount of vinyl POSS added is 5% of the mass of the outer layer polymer powder, and the amount of zinc chloride added is 0.002% of the mass of the vinyl POSS; extruding the inner layer polymer powder and the cross-linked mixture through different screw machines, and the inner layer polymer and the cross-linked mixture after extrusion by the screw machine enter the core-skin composite spinning assembly through flow channels respectively; (3) The inner layer polymer and the cross-linked mixture are sequentially ejected through a spinneret with a pore size of 0.1 mm to form a primary fiber with a heterogeneous structure, wherein the inner layer polymer accounts for 80% of the cross-sectional area of the primary fiber and the outer layer cross-linked polymer accounts for 20% of the cross-sectional area of the primary fiber; (4) The as-spun fibers were post-treated by microwave heating at a microwave power of 200 W, a heating temperature of 150 °C, and a post-treatment time of 4 h to obtain liquid crystal polymer fibers.
[0068] Example 2 The difference between this embodiment and embodiment 1 is that in step (3), the inner layer polymer accounts for 85% of the cross-sectional area of the spun fiber, and the outer layer cross-linked polymer accounts for 15% of the cross-sectional area of the spun fiber.
[0069] Example 3 The difference between this embodiment and embodiment 1 is that in step (3), the inner layer polymer accounts for 90% of the cross-sectional area of the spun fiber, and the outer layer cross-linked polymer accounts for 10% of the cross-sectional area of the spun fiber.
[0070] Example 4 Liquid crystal polymer fibers were prepared as follows: (1) preparing an inner layer polymer and an outer layer polymer respectively, wherein the inner layer polymer is prepared as follows: adding 65 mol% of 6-hydroxy-1-naphthoic acid, 20 mol% of m-hydroxybenzoic acid, and 15 mol% of resorcinol into a reaction kettle, passing nitrogen to deoxygenate, heating to 230°C, and stirring at a speed of 400 r / min for 60 min; after uniform mixing, adding calcium acetate, continuing to stir for 60 min, evacuating, and melt copolymerizing for 1.5 h, wherein the amount of calcium acetate added is 0.007% of the mass of 6-hydroxy-1-naphthoic acid; after the reaction is completed, naturally cooling to room temperature to obtain the inner layer polymer, and then crushing the inner layer polymer to obtain inner layer polymer powder.
[0071] The outer layer polymer is prepared as follows: 65 mol% of 6-hydroxy-1-naphthoic acid, 15 mol% of 4,4-biphenyldicarboxylic acid, and 20 mol% of 4-allylcatechol are added to a reactor, nitrogen is passed to deoxygenate, the temperature is raised to 230°C, and the mixture is stirred at a speed of 400 r / min for 60 minutes; after uniform mixing, calcium acetate is added, stirring is continued for 60 minutes, vacuumization is performed, and melt copolymerization is performed for 1.5 hours, and the amount of calcium acetate added is 0.007% of the mass of 6-hydroxy-1-naphthoic acid; after the reaction is completed, the mixture is naturally cooled to room temperature to obtain the outer layer polymer. Then, the outer layer polymer is crushed to obtain the outer layer polymer powder.
[0072] (2) Adding vinyl POSS and zinc chloride to the outer layer polymer powder to form a cross-linked mixture, wherein the amount of vinyl POSS added is 8% of the mass of the outer layer polymer powder, and the amount of zinc chloride added is 0.003% of the mass of the vinyl POSS; extruding the inner layer polymer powder and the cross-linked mixture through different screw machines, and the inner layer polymer and the cross-linked mixture after extrusion by the screw machine enter the core-skin composite spinning assembly through flow channels respectively; (3) The inner layer polymer and the cross-linked mixture are sequentially ejected through a spinneret with a pore size of 0.1 mm to form primary fibers with a heterogeneous structure, in which the inner layer polymer accounts for 85% of the cross-sectional area of the primary fibers and the cross-linked mixture accounts for 15% of the cross-sectional area of the primary fibers.
[0073] (4) The as-spun fibers were post-treated by microwave heating at a microwave power of 400 W, a heating temperature of 170 °C, and a post-treatment time of 3 h to obtain liquid crystal polymer fibers.
[0074] Example 5 Liquid crystal polymer fibers were prepared as follows: (1) preparing an inner layer polymer and an outer layer polymer respectively, wherein the inner layer polymer is prepared as follows: adding 70 mol% of 5-hydroxy-2-naphthoic acid, 15 mol% of 4-hydroxyphenylacetic acid, and 15 mol% of 1,4-naphthalene diol into a reaction kettle, passing nitrogen to deoxygenate, heating to 250°C, and stirring at a speed of 600 r / min for 30 min; after mixing evenly, adding calcium acetate, continuing to stir for 30 min, evacuating, and melt copolymerizing for 1 h, wherein the amount of calcium acetate added is 0.01% of the mass of 5-hydroxy-2-naphthoic acid; after the reaction is completed, naturally cooling to room temperature to obtain the inner layer polymer, and then crushing the inner layer polymer to obtain inner layer polymer powder.
[0075] The outer layer polymer is prepared as follows: 70 mol% of 5-hydroxy-2-naphthoic acid, 15 mol% of terephthalic acid, and 15 mol% of 4-allyl catechol are added to a reactor, nitrogen is passed to deoxygenate, the temperature is raised to 250°C, and the mixture is stirred at a speed of 600 r / min for 30 minutes; after uniform mixing, calcium acetate is added, stirring is continued for 30 minutes, vacuumization is performed, and melt copolymerization is performed for 1 hour, and the amount of calcium acetate added is 0.01% of the mass of 5-hydroxy-2-naphthoic acid; after the reaction is completed, the mixture is naturally cooled to room temperature to obtain the outer layer polymer. Then, the outer layer polymer is crushed to obtain the outer layer polymer powder.
[0076] (2) Adding vinyl POSS and zinc chloride to the outer layer polymer powder to form a cross-linked mixture, wherein the amount of vinyl POSS added is 10% of the mass of the outer layer polymer powder, and the amount of zinc chloride added is 0.004% of the mass of the vinyl POSS; extruding the inner layer polymer powder and the cross-linked mixture through different screw machines, and the inner layer polymer and the cross-linked mixture after extrusion by the screw machine enter the core-skin composite spinning assembly through flow channels respectively; (3) The inner layer polymer and the cross-linked mixture are sequentially ejected through a spinneret with a pore size of 0.1 mm to form primary fibers with a heterogeneous structure, in which the inner layer polymer accounts for 90% of the cross-sectional area of the primary fibers and the cross-linked mixture accounts for 10% of the cross-sectional area of the primary fibers.
[0077] (4) The as-spun fibers were post-treated by microwave heating at a microwave power of 500 W, a heating temperature of 180 °C, and a post-treatment time of 2 h to obtain liquid crystal polymer fibers.
[0078] Example 6 The difference between this embodiment and embodiment 1 is that in step (4), the as-spun fibers are only subjected to a heat treatment, and the heating temperature and the post-treatment time remain unchanged.
[0079] Comparative Example 1 Liquid crystal polymer fibers were prepared as follows: 60 mol% of 2-hydroxy-6-naphthoic acid, 20 mol% of p-hydroxybenzoic acid, and 20 mol% of hydroquinone are added to the reactor, nitrogen is passed to deoxygenate, and the temperature is raised to 200°C, and stirred at a speed of 500 r / min for 50 minutes; after uniform mixing, calcium acetate is added, stirring is continued for 50 minutes, vacuum is drawn, and melt copolymerization is carried out for 2 hours. The amount of calcium acetate added is 0.005% of the mass of 2-hydroxy-6-naphthoic acid; after the reaction is completed, it is naturally cooled to room temperature to obtain a liquid crystal polymer, and then the liquid crystal polymer is crushed to obtain a polymer powder. (2) The polymer powder is extruded through a screw machine and sprayed out through a single-hole nozzle assembly to form primary fibers; (3) The as-spun fibers were post-treated by microwave heating at a microwave power of 200 W, a heating temperature of 150 °C, and a post-treatment time of 4 h to obtain liquid crystal polymer fibers.
[0080] Comparative Example 2 The difference between this comparative example and Example 1 is that in step (2), vinyl POSS and zinc chloride are not added to the outer layer polymer powder, and the cross-linking mixture in the subsequent steps contains only the outer layer polymer powder.
[0081] Comparative Example 3 Liquid crystal polymer fibers were prepared as follows: (1) 60 mol% of 2-hydroxy-6-naphthoic acid, 20 mol% of 5-methylisophthalic acid and 20 mol% of 2-allylbenzene-1,4-diol are added to a heat-resistant and pressure-resistant reactor, nitrogen is introduced for deoxygenation, the temperature is raised to 200°C, stirring is started, the stirring speed is 500 r / min, and the stirring time is 50 min; after uniform mixing, calcium acetate is added, stirring is continued for 50 min, vacuum is drawn, and melt copolymerization is carried out for 2 h, and the amount of calcium acetate added is 0.005% of the mass of 2-hydroxy-6-naphthoic acid; after the reaction is completed, the reaction is naturally cooled to room temperature to obtain a liquid crystal polymer, and the liquid crystal polymer is then crushed to obtain a polymer powder.
[0082] (2) adding vinyl POSS and zinc chloride to the polymer powder to form a cross-linked mixture, wherein the amount of vinyl POSS added is 5% by weight of the outer layer polymer powder, and the amount of zinc chloride added is 0.002% by weight of the vinyl POSS; (3) The cross-linked mixture is extruded through a screw machine and then sprayed out through a single-hole nozzle assembly to form primary fibers; (4) The as-spun fibers were post-treated by microwave heating at a microwave power of 200 W, a heating temperature of 150 °C, and a post-treatment time of 4 h to obtain liquid crystal polymer fibers.
[0083] Comparative Example 4 The difference between this embodiment and embodiment 1 is that in step (3), the inner layer polymer accounts for 95% of the cross-sectional area of the spun fiber, and the outer layer cross-linked polymer accounts for 5% of the cross-sectional area of the spun fiber.
[0084] Experimental example The liquid crystal polymer fibers prepared in Examples 1-6 and Comparative Examples 1-4 were tested, wherein the mechanical properties were tested using a universal mechanical testing machine (electronic universal testing machine CMT6103), and the breaking strength of the fiber was tested with reference to the standard GB / T19975-2005 "Test method for tensile properties of high-reinforced filaments", and the hooking strength of the fiber was tested with reference to the standard GB / T 14344-2008 "Test method for tensile properties of chemical fiber filaments". The melting point of the fiber was measured using a Mettler Toledo differential scanning calorimeter (DSC); the dielectric constant was measured using a dielectric constant tester (the measurement frequency was 100 MHZ); the wear resistance was measured using a Y109-Ⅱ yarn abrasion tester (the weight was 30 g, and the sandpaper model was 400). The breaking strength was measured after 5000 frictions, and the strength retention rate was calculated. The strength retention rate was calculated as follows: breaking strength after friction / breaking strength before friction*100%, and the wear resistance of the fiber was expressed as the strength retention rate. The test results are shown in Table 1.
[0085] Table 1
[0086] From Table 1 we can see that: According to the test results of Examples 1, 4-5, the liquid crystal polymer fiber of the present invention has a moderate melting point, good mechanical properties (breaking strength before friction, hook strength) and wear resistance, and a relatively low dielectric constant.
[0087] From the test results of Examples 1-3 and Comparative Example 4, it can be seen that when the content of the outer cross-linked polymer in Examples 1-3 is 10-20%, as the content of the outer cross-linked polymer increases, the hook strength, melting point, and wear resistance of the fiber will also increase, and the pre-friction breaking strength and dielectric constant will decrease accordingly, which means that the addition of the outer cross-linked polymer can effectively enhance the bending resistance, temperature resistance, wear resistance, and dielectric properties of the fiber; but the increase in the content of the outer cross-linked polymer will also lead to a decrease in the breaking strength of the fiber. In Comparative Example 4, when the outer cross-linked polymer only accounts for 5% of the cross-sectional area of the primary fiber, although the breaking strength is high, due to the low proportion of the outer cross-sectional area, the hook strength is small, the wear resistance is limited, and the dielectric constant is high.
[0088] According to the test results of Example 1 and Example 6, compared with Example 1, the microwave radiation treatment was omitted in the post-treatment of Example 6, and the various properties of the fiber were slightly reduced.
[0089] According to the test results of Example 1 and Comparative Examples 1-3, compared with Example 1, Comparative Example 1 only uses a single inner layer of liquid crystal polymer, the mechanical properties of the fiber are lower, and during the friction process, the fiber surface is prone to fluffing and splitting, resulting in poor wear resistance and a high dielectric constant; Comparative Example 3 uses an outer layer of cross-linked polymer, and the resulting fiber has good dielectric properties, wear resistance and hook strength, but low pre-friction breaking strength and high melting point. Although Comparative Example 2 uses a double layer of liquid crystal polymer, because no cross-linking agent is introduced into the liquid crystal polymer, the fiber has poor properties except for a high pre-friction breaking strength.
[0090] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength and wear-resistant liquid crystal polymer fiber, characterized in that: It comprises an inner layer polymer and an outer layer cross-linked polymer coated on the surface of the inner layer polymer, and the molecular structure formula of the outer layer cross-linked polymer is: 。 2. The high-strength and wear-resistant liquid crystal polymer fiber according to claim 1, characterized in that: The inner layer polymer accounts for 80-90% of the cross-sectional area of the high-strength and wear-resistant liquid crystal polymer fiber, and the outer layer cross-linked polymer accounts for 10-20% of the cross-sectional area of the high-strength and wear-resistant liquid crystal polymer fiber.
3. The high-strength and wear-resistant liquid crystal polymer fiber according to claim 1, characterized in that: The outer layer cross-linked polymer includes an outer layer polymer, a cross-linking agent, and a catalyst; the added amount of the cross-linking agent is 5-10% of the mass of the outer layer polymer, and the added amount of the catalyst is 0.002-0.004% of the mass of the cross-linking agent.
4. The high-strength and wear-resistant liquid crystal polymer fiber according to claim 3, characterized in that: The cross-linking agent is vinyl-POSS, and the catalyst is at least one of zinc chloride, aluminum chloride and tin chloride.
5. The high-strength and wear-resistant liquid crystal polymer fiber according to claim 3, characterized in that: The inner layer polymer and the outer layer polymer are both prepared by melt copolymerization, wherein, based on molar mass, the components of the inner layer polymer include 60-70% of monomers with naphthalene rings, 10-20% of monomers with benzene rings, and 10-20% of diphenol monomers; the components of the outer layer polymer include 60-70% of monomers with naphthalene rings, 10-20% of diacid monomers, and 10-20% of double bond monomers.
6. The high-strength and wear-resistant liquid crystal polymer fiber according to claim 5, characterized in that: The naphthalene ring-bearing monomer is at least one of 2-hydroxy-6-naphthoic acid, 6-hydroxy-1-naphthoic acid, 7-hydroxy-2-naphthoic acid, and 5-hydroxy-2-naphthoic acid; The benzene ring-bearing monomer is at least one of p-hydroxybenzoic acid, m-hydroxybenzoic acid, and 4-hydroxyphenylacetic acid; The diphenol monomer is at least one of hydroquinone, resorcinol and 1,4-benzene; The diacid monomer is at least one of 5-methylisophthalic acid, 4,4-biphenyldicarboxylic acid, and terephthalic acid; The double bond monomer is at least one of 2-allylbenzene-1,4-diol and 4-allylcatechol.
7. The high-strength and wear-resistant liquid crystal polymer fiber according to claim 1, characterized in that: The molecular structure formula of the inner layer polymer is: 。 8. A method for preparing high-strength and wear-resistant liquid crystal polymer fiber, characterized in that: The steps include: (1) preparing an inner layer polymer and an outer layer polymer respectively; (2) uniformly mixing the outer layer polymer, the crosslinking agent, and the catalyst to prepare a crosslinking mixture; extruding the inner layer polymer and the crosslinking mixture separately and supplying them to a sheath-core composite spinning assembly; (3) The inner layer polymer and the cross-linked mixture are sequentially ejected through the spinneret of the core-skin composite spinning assembly to form primary fibers; (4) Post-processing the as-spun fibers to obtain high-strength and wear-resistant liquid crystal polymer fibers.
9. The method for preparing high-strength and wear-resistant liquid crystal polymer fiber according to claim 8, characterized in that: In step (1), the preparation of the inner layer polymer and the outer layer polymer comprises the following steps: adding the components of the inner layer polymer / the outer layer polymer into a reaction container, heating to 200-250°C under nitrogen flow, and stirring at a speed of 400-600 r / min for 30-60 min; after uniform mixing, adding an esterification catalyst, continuing stirring for 30-60 min, evacuating, and melt copolymerizing for 1-2 h; after the reaction is completed, naturally cooling to room temperature to obtain the inner layer polymer / the outer layer polymer; In step (4), the post-treatment includes microwave radiation treatment and heating treatment; the microwave radiation power is 200-500 W; the heating treatment temperature is 150-180° C., and the post-treatment time is 2-4 h.
10. The method for preparing high-strength and wear-resistant liquid crystal polymer fiber according to claim 8, characterized in that: The esterification catalyst is at least one of calcium acetate, magnesium acetate and zinc acetate; The components of the inner layer polymer and the outer layer polymer both include naphthalene ring-bearing monomers, and the added amount of the esterification catalyst is 0.005-0.01% of the mass of the naphthalene ring-bearing monomers in the inner layer polymer / outer layer polymer.